Agricultural Extension Governance and Services in Responding to Problems of the Agricultural Sector and Extension Institutions - Subejo Subejo; Hanita Athasari Zain; Najmu Tsaqib Akhda; Ishadiyanto Salim; Agrit Kirana Bunda; Pristianti Krisna Guslimantasya; Septi Nurhasanah; Fairuz Husna Aida; Beny Nabila Happy Fauziah (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
Agricultural extension services that are currently following the decentralization era require a participatory extension approach in line the needs of farmers in each region. This mixed-method study looked at the condition of agricultural extension governance and services at local level which characterized by agricultural resource based on economic development, namely Purworejo Regency, Central Java Province, in responding to problems in the agricultural sector and extension institutions. The research results show that the governance of extension services in Purworejo Regency faces the issue of lack of capacity building o extension agents with excessive workload and minimal staff. In contrast, extension agents have a pile of tasks that must be done individually, without inadequate support on facilities and sufficient budget to support extension services to farmers. The impact of climate change, such as an increase in pests and plant diseases and water crisis, have become major problems in the agricultural sector. This study suggests a policy and program to build extension agents' capacity and a more organized governance of extension institutions.